Pengaruh Ukuran Perusahaan, Profitabilitas dan Leverage Terhadap Tax Avoidance Pada Perusahaan Batu Bara Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Febrianti, Rindi Antika; Pramiana, Omi (Universitas Muhammadiyah Gresik, 2025)
This study aims to analyze the effect of firm size, profitability, and leverage on tax avoidance in coal mining companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. Tax avoidance, a legal strategy to minimize tax obligations, is measured using the Effective Tax Rate (ETR), with independent variables including firm size (total assets), profitability (ROA), and leverage (DER). The research employs a quantitative method with multiple linear regression analysis, utilizing secondary data from the annual financial reports of 20 purposively selected companies. The results indicate that firm size and profitability significantly influence tax avoidance, while leverage has no significant effect.